‘Urban planning as the first step of architecture’ a response to the mass housing issue and the quality of its interior landscape: The Case Study of Pouillon’s Housing Estate ‘Diar El Mahçoul’ in Algiers - Tehami, Mohamed; Anouche, Karima (ZARCH, 2017)
The problem of mass housing dates back to the fifties as a crisis of the modern movement. Several responses have been proposed through the charters of CIAM where the future of the mass housing construction was in standardization and heavy industrialization in the image of mass production system. This created a separation between the housing itself and its environment. Meanwhile, Fernand Pouillon, far from theoretical debates, was able to find answers to the mass housing production issue by returning to the design (composition) of the traditional city, where urban planning established the art of architecture, and housing with its inner landscape as a part of the city. Through the analysis of the housing estate Diar El Mahçoul of Fernand Pouillon, we will try to understand the modern vision of the future of housing, which were his references, his tools and how did he manage to do it? KEYWORDS: Architectural composition, architecture and urban planning, housing estate and city, mass housing, Diar El Mahçoul, Fernand Pouillon.